Relationship of hepatic fibrosis, cirrhosis, and mortality with cholecystectomy in patients with hepatitis C virus infection. Issue 2 (February 2016) - Martin, Donald J.; Weideman, Rick; Crook, Terri; Brown, Geri
Abstract : Objectives: Studies have suggested that cholecystectomy is a risk factor for nonalcoholic fatty liver disease, but it is not known whether cholecystectomy is a risk factor for the progression of other chronic liver diseases such as hepatitis C virus (HCV) infection. The aim of this study was to assess whether cholecystectomy is associated with an increase in fibrosis, cirrhosis, and cirrhosis-related complications in patients with chronic HCV infection. Methods: Among a total of 3989 HCV-positive patients at the VA North Texas Health Care System, we retrospectively reviewed the records of 88 patients who had undergone cholecystectomy between 1998 and 2013, followed up for a median of 4.9 years. We compared the outcomes of these patients with those of two age-matched, race-matched, and sex-matched cohorts: a cohort consisting of 129 HCV-positive patients without gallbladder disease (GBD) and a second cohort consisting of 178 HCV-positive patients with GBD who had not undergone cholecystectomy. Demographics, presence of metabolic syndrome, alcohol use, laboratory data, and clinical progression of liver disease were compared at study entry and 5 years later. Results: Controlling for multiple factors associated with increase in liver fibrosis, analyses confirmed that a there was an increase in the proportion of patients who developed cirrhosis [odds ratio (OR)=3.24, 95% confidence interval (CI) 1.57–6.68, P =0.001] and ascites (OR=3.01, 95% CI 1.14–7.97, P =0.026) as well as in the incidence of death (OR=6.29, 95% CI 2.13–18.59, P =0.001) 5 years after cohort entry among HCV-positive patients with cholecystectomy compared with HCV-positive controls. The HCV-positive patient group with previous cholecystectomy showed an increased incidence of cirrhosis (OR=2.43, 95% CI 1.34–4.41, P =0.004), hepatocellular carcinoma (OR=2.85, 95% CI 1.11–7.36, P =0.030), and death (OR=3.31, 95% CI 1.50–7.28, P =0.003) 5 years after cohort entry compared with HCV-positive controls with GBD who had not undergone cholecystectomy. Conclusion: Cholecystectomy among HCV-positive patients is associated an increased incidence of fibrosis, cirrhosis, and its complications (ascites, hepatocellular carcinoma, and death) compared with HCV-positive controls and HCV-positive patients with GBD who have not undergone cholecystectomy.